2012
DOI: 10.1007/s11033-012-2254-z
|View full text |Cite
|
Sign up to set email alerts
|

Significant association between GSTT1 null genotype and risk of asthma during childhood in Caucasians

Abstract: Asthma is a complex multifactorial disorder and its management requires a better understanding of its various pathogenesis and mechanisms. Previous studies assessing the association between glutathione S-transferase T1 (GSTT1) null genotype and asthma risk during childhood reported conflicting results. To get a more precise estimation of the association between GSTT1 null genotype and risk of asthma during childhood, we performed a meta-analysis of 16 studies with a total of 18,558 subjects. Subgroup analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Their findings do not support a substantial individual role of GST genes in the development of asthma. Similarly, Zhao Y. et al . found that the GSTT1 null genotype was associated with increased risk of asthma during childhood in Caucasians.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Their findings do not support a substantial individual role of GST genes in the development of asthma. Similarly, Zhao Y. et al . found that the GSTT1 null genotype was associated with increased risk of asthma during childhood in Caucasians.…”
Section: Discussionmentioning
confidence: 86%
“…After these two meta‐analyses were published, several additional case–control studies were performed. Zhao Y. et al . included 16 studies to recently investigate the relationship between the GSTT1 polymorphism and risk of asthma during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Also, in other inflammatory-driven diseases, such as asthma or type 2 diabetes mellitus, an increased susceptibility was found with the GSTT1null genotype. 26,27 In this meta-analyses, we showed that the Figure 4 Forest plot of the association of the GSTT1null genotype with ulcerative colitis (UC). Effect of the GSTT1null genotype on the risk of UC (odds ratios (ORs) and the 95% confidence intervals (CIs)) for each study is shown.…”
Section: Figurementioning
confidence: 85%
“…Another reported null findings for GSTT1 interaction among children for particulate matter exposure from anthropogenic and non-anthropogenic sources and peak expiratory flow volume [ 23 ]. A recent meta-analysis including studies that investigated GSTT1 polymorphisms and asthma found that regardless of TRAP exposure, carriers of GSTT1 null mutation had an increased risk of childhood asthma [ 21 ]. To the best of our knowledge, ours is the first study to show TRAP exposure during the first year of life increasing risk of asthma and wheeze in late childhood among carriers of GSTT1 null polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have reported interaction effects for GSTM1 evaluated jointly with other oxidative stress genes [ 12 , 19 ]. While the importance of GSTT1 gene polymorphisms in influencing the development of asthma has been recognized [ 20 , 21 ], evidence concerning the modifying effect of GSTT1 polymorphisms on the association between TRAP exposure and respiratory and allergic diseases has been published only twice, with both studies reporting null findings [ 22 , 23 ]. Past studies have investigated the interaction between GST genes and TRAP exposures on risk of asthma in birth cohort [ 14 , 15 , 22 ] and cross-sectional studies [ 10 , 11 , 18 , 23 ].…”
Section: Introductionmentioning
confidence: 99%